Implementation of the Moodle System Into EFL Classes (2017)
This study aims to examine students’ perception on using the Moodle system in secondary school in English as a foreign language lessons. A mixed method approach was used in this study with qualitative and quantitative research models. The study group consisted of 333 students and 12 English language teachers. The quantitative data were collected by a survey and qualitative data were collected by five open-ended questions. The results showed that students in general perceive themselves as sufficient in terms of the Moodle system and teachers thought that the system was contemporary and beneficial in the long run but at the time of the study it was not functioning well.